Bullet Penetration In The Face Caused By Accidental Gunshot: A Case Report - Sastrasupena, Aditya Herwandar; Bangun, Kristaninta (Lingkar Studi Bedah Plastik Foundation, 2013)
Background: Clinical and radiological examinations are used to predict the location of the bullet in bullet penetration injury. The maxillofacial region had a variety of structure which could make the bullet deviate from its normal trajectories. Patient and Methods: A rare case of bullet penetration in the face caused by accidental gunshot is described. A 32 year-old male was hit by a bullet in the face with entrance wound on the left temporal region. Radiologic examination showed a bullet in the left inferior orbita. Treatment was exploration and extraction of the bullet. In this case we observe the difference between the clinical examination, radiological diagnosis and intraoperative findings Result: The patient underwent an explorative operation based on the prediction of location of the bullet from the clinical and radiological examination. The bullet was found in the inferior rectus muscle which the location is out of the prediction of clinical examination and radiologic findings. Summary: Clinical and radiological examination do not always give the accurate prediction regarding the location of bullet in penetrating bullet injury of the face because the face has a variety of bone, muscle and soft tissue structure.